DEVELOPING LEARNER AUTONOMY ONLINE THROUGH MICRO BLOGGING EDMODO - Pryla Rochmahwati (Jurnal Bahasa Lingua Scientia, 2014)
Social changes and development of technology force EFL teachers’ struggle to utilize potentially useful technology and promote learner autonomy. Edmodo as a highly versatile micro blogging platform is needed to develop learner autonomy in virtual learning environments. Keeping this need in mind, this paper reports on the attempt to develop learner autonomy online of 65 EFL learners in the fifth semester of English Department in STAIN Ponorogo through Edmodo. Data were collected through observations and the analyses of the observations light on the overall experience of learning with Edmodo especially through the lens of learner autonomy. The results showed that Edmodo afforded students the opportunity to take responsibility for their own learning and involve them in taking ownership (partial or total) of many learning processes. However, lack of access to internet and the ambiguous task instruction also contributed to a limited level of social interaction in virtual learning environments. Finally, it can be concluded that well-designed tasks and accessibility to internet are essential to maximize the potentials of Edmodo for learner autonomy.